2004
DOI: 10.1128/aem.70.6.3521-3527.2004
|View full text |Cite
|
Sign up to set email alerts
|

Specific 12β-Hydroxylation of Cinobufagin by Filamentous Fungi

Abstract: Biotransformation of natural products has great potential for producing new drugs and could provide in vitro models of mammalian metabolism. Microbial transformation of the cytotoxic steroid cinobufagin was investigated. Cinobufagin could be specifically hydroxylated at the 12␤-position by the fungus Alternaria alternata. Six products from a scaled-up fermentation were obtained by silica gel column chromatography and reversed-phase liquid chromatography and were identified as 12␤-hydroxyl cinobufagin, 12␤-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Some studies demonstrated that huachansu injection can improve the QOL of patients and has been used as a treatment of cancer in China [26][27][28] . It was reported that digitalis-like cinobufagin can protect prostate cancer cells from proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that huachansu injection can improve the QOL of patients and has been used as a treatment of cancer in China [26][27][28] . It was reported that digitalis-like cinobufagin can protect prostate cancer cells from proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The media were sterilized at 121 8C and 1.06 kg/cm 2 for 30 min. [20] The strains were maintained on potato dextrose agar slants at 4 8C.…”
Section: Experimental Section Apparatus and Reagentsmentioning
confidence: 99%
“…4, 5 and 6 were identified as 12b -hydroxy-desacetylcinobufagin, 3-oxo-12a-hydroxybufagin and 12b-hydroxybufagin, respectively, by comparison with the literature [10] and on the basis of various spectroscopic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Cunninghamella elegans has been employed for the biotransformation of cinobufagin (1) to afford 5 metabolites. The structures of the transformation products have been characterized as 12a -hydroxybufagin (2), 11a -hydroxybufagin (3), 12b -hydroxy-desacetylcinobufagin (4), 3-oxo-12a -hydroxybufagin (5) and 12b -hydroxybufagin (6) [10] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%